2021
DOI: 10.4143/crt.2020.1356
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy–Guided Bladder-Sparing Treatment for Muscle-Invasive Bladder Cancer: Results of a Pilot Phase II Study

Abstract: Reduced quality of life after cystectomy has made bladder preservation a popular research topic for muscle-invasive bladder cancer (MIBC). Previous research has indicated significant tumor downstaging after neoadjuvant chemotherapy (NAC). However, maximal transurethral resection of bladder tumor (TURBT) was performed before NAC to define the pathology, impacting the real evaluation of NAC. This research aimed to assess real NAC efficacy without interference from TURBT and apply combined modality therapies guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…In 64 chemoradiotherapy patients, the probability of surviving metastasis-free by 36 months (i.e., 3-year MFS rate) was encouraging as 70%. The outcomes obtained here compared favorably to those reported in studies involving neoadjuvant chemotherapy for MIBC [ 11 ].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In 64 chemoradiotherapy patients, the probability of surviving metastasis-free by 36 months (i.e., 3-year MFS rate) was encouraging as 70%. The outcomes obtained here compared favorably to those reported in studies involving neoadjuvant chemotherapy for MIBC [ 11 ].…”
Section: Discussionsupporting
confidence: 63%
“…Although the idea of neoadjuvant chemotherapy followed by concurrent chemoradiotherapy is dated [ 15 16 ], its benefit remains unclear. On the premise of tolerable chemotherapy regimen, studies suggested that patients with downstaging by neoadjuvant chemotherapy could benefit from bladder preservation chemoradiotherapy [ 11 17 ], as well as from radical cystectomy [ 3 4 18 ]. In order to improve the outcomes of neoadjuvant chemotherapy, the addition of immune checkpoint inhibitors to cisplatin-based chemotherapy is a promising strategy.…”
Section: Discussionmentioning
confidence: 99%
“…There is an ongoing debate on the routine utilization of NAC in cisplatin-eligible patients who wish to undergo CMT [ 33 , 34 , 35 ]. The practice often adopted in clinical settings is to administer NAC to patients with MIBC who are fit for cisplatin and offer CMT to those who responded to NAC [ 36 , 37 , 38 ]. Similar selection criteria have been proposed in the SPARE Trial design ( Figure 1 ) [ 39 ].…”
Section: Potential Candidatesmentioning
confidence: 99%
“…In a phase II study carried out by Shi et al. with the purpose to assess the efficiency of NAC-guided bladder-sparing treatment in MIBC patients, 6 patients who achieved cCR underwent TURBT plus concurrent CRT and all survived with a functional bladder in a median follow-up of 44.6 months ( 76 ). These findings demonstrated the feasibility and safety of bladder preservation strategy in highly selected cCR MIBC patients.…”
Section: Disease Management Of Clinical Complete Responders To Neoadj...mentioning
confidence: 99%